O-19 Community volunteering in adult hospices: analysis of the extent, benefits and barriers. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Scott, Ros; Hindmarch, Jean
Abstract : Background: Hospice volunteers have become increasingly involved in supporting patients, families and carers in the community. There is little known about the extent, structure and benefits of such services, or of barriers to development. Hospice UK undertook a mapping survey as part of a larger project. Aims: The aims were to: map the extent of hospice community volunteering services gather information about services already in place identify barriers to developing services inform the development of resources for hospices interested in establishing community volunteering services. Methods: A 40 item online questionnaire was developed, reviewed by the project reference group, piloted and revised. Comprising multiple choice and open-ended questions, it was circulated to the full membership of Hospice UK; 225 hospices including 14 combined adult and children's services and 25 children's hospices. Quantitative analysis was undertaken using both the online survey data output and Excel. Qualitative data were analysed using a framework approach. Children's hospice data were analysed and reported separately. Findings from adult hospices: 115 adult hospices responded 70% had community volunteering services (CVS) 61% of hospices without CVS were keen to develop these the majority of hospice CVS were staff–led. Benefits included: improved wellbeing for patients, families and volunteers respite for families/carers improved access to a range of services for patients and families improved quality of care staff having greater understanding of patients' and family needs staff skills and time more effectively used increased service provision. Barriers to development included: lack of resources (including funding, staff, volunteers and time) concern over lone–working, safeguarding and insurance. Respondents indicated that they would find materials to guide development helpful. Conclusions: Hospice community volunteering services appear to be widespread and growing. There are clear benefits for patients, families, volunteers, organisations and staff.